Pengaruh Viral Marketing, Brand Image, Product Quality, Terhadap Keputusan Pembelian Product Somethinc (Studi Kasus Pada Mahasiswa FEB Unisma) - Maghfirah, Inayatul; Priyono, Achmad Agus; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Viral Marketing, Brand Image, and Product Quality on the purchasing decisions of Somethinc products among students of the Faculty of Economics and Business at the Islamic University of Malang (FEB UNISMA). Somethinc is a local skincare brand that has successfully emerged through digital marketing strategies, viral content, and support from beauty influencers. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 130 respondents who are users of Somethinc products and active students of FEB UNISMA. The data analysis technique used was multiple linear regression with the help of SPSS software. The results show that simultaneously, Viral Marketing, Brand Image, and Product Quality have a significant influence on purchasing decisions. Partially, each variable also has a positive and significant impact. These findings highlight that effective digital marketing strategies, a strong Brand Image, and high Product Quality play a crucial role in increasing consumer purchasing decisions. This research is expected to serve as a practical reference for companies in designing targeted marketing strategies and as a theoretical contribution for future studies in the field of marketing management. Keywords: Viral Marketing, Brand Image, Product Quality, Purchasing Decision, Somethinc